Molecular insight into invasive group A streptococcal disease - Cole, Jason N.; Barnett, Timothy C.; Nizet, Victor; Walker, Mark J. (Nature reviews. Microbiology, 2011)
Key Points Streptococcus pyogenes , also called group A Streptococcus (GAS), is a Gram-positive bacterial pathogen that naturally infects only humans and is the aetiological agent of several potentially fatal syndromes, including 'flesh-eating disease' (necrotizing fasciitis). The worldwide resurgence of severe invasive GAS infections over the past 30 years is correlated with the global dissemination of the GAS serotype M1T1 clone. Recent work demonstrates that the capacity of GAS serotype M1T1 to cause invasive disease is increased by selection for mutations within the covRS two-component regulator operon. This genetic alteration dramatically changes the transcriptome, resulting in the downregulation of a broad-spectrum cysteine protease, streptococcal pyrogenic exotoxin B (SpeB), and the upregulation of several virulence factors, including the nuclease extracellular streptodornase D (Sda1). Elevated Sda1 nuclease activity enhances the resistance of GAS serotype M1T1 to neutrophil-mediated killing, through the degradation of DNA-based neutrophil extracellular traps, and the absence of SpeB protease activity permits the accumulation of plasmin activity on the GAS cell surface, triggering tissue destruction and systemic spread. GAS uses a repertoire of virulence factors to thwart the host innate immune response, and several of these factors are critical for invasive disease. The switch from non-invasive to hyperinvasive GAS is triggered by particular genetic events, and our increased understanding of this switch has led to a model for the initiation of invasive GAS disease in humans. An understanding of the mechanism by which GAS causes serious invasive infections may augment the development of new-generation therapeutics and provide better health outcomes in the fight against this globally important human pathogen. Group A Streptococcus can cause devastating infections with high mortality rates. Here, Walker and colleagues describe the bacterial virulence factors that allow this species to infect tissues and escape destruction in neutrophils, and discuss how genetic changes in a two-component regulatory system promote pathogenicity. Streptococcus pyogenes is also known as group A Streptococcus (GAS) and is an important human pathogen that causes considerable morbidity and mortality worldwide. The GAS serotype M1T1 clone is the most frequently isolated serotype from life-threatening invasive (at a sterile site) infections, such as streptococcal toxic shock-like syndrome and necrotizing fasciitis. Here, we describe the virulence factors and newly discovered molecular events that mediate the in vivo changes from non-invasive GAS serotype M1T1 to the invasive phenotype, and review the invasive-disease trigger for non-M1 GAS. Understanding the molecular basis and mechanism of initiation for streptococcal invasive disease may expedite the discovery of novel therapeutic targets for the treatment and control of severe invasive GAS diseases.